Placental growth factor in patients with decreased renal function - Zakiyanov, Oskar; Kalousová, Marta; Zima, Tomáš; Tesař, Vladimír (Renal failure, 2011)
BACKGROUND: Patients with decreased renal function are characterized by high cardiovascular morbidity and mortality due to complications of premature atherosclerosis. Placental growth factor (PlGF) is a proatherogenic cytokine and new biomarker of cardiovascular events. The aim of this study was to determine PlGF levels and describe their relationship to renal function and risk factors of atherogenesis in patients with decreased renal function. METHODS: The study group consisted of 114 subjects: 45 patients with various degrees of decreased renal function (CHRI), 31 long-term hemodialysis (HD) patients, and 38 age-matched healthy control subjects. PlGF was assessed immunochemically (enzyme-linked immunosorbent assay) and routine biochemical parameters were measured using standard laboratory methods. RESULTS: PlGF levels were significantly increased in CHRI and HD patients compared to controls (10.5 ± 3.3 pg/mL in CHRI patients and 11.5 ± 3.4 pg/mL HD patients vs. 8.1 ± 1.8 pg/mL in controls, both p < 0.0001). In CHRI patients, PlGF was detectable in the urine, and its urine concentration correlated with its serum levels. In HD patients, PlGF correlated with low-density lipoproteins (r = 0.36, p < 0.05), but was not related to C-reactive protein levels. Higher levels of PlGF were found in CHRI patients with cardiovascular disease, compared with those free of such complication. CONCLUSIONS: PlGF levels are increased in patients with decreased kidney function. PlGF is detectable in the urine, and serum and urine levels of PlGF are significantly interrelated. It is higher in CHRI patients with cardiovascular disease. Further studies are required to demonstrate the usefulness and significance of PlGF in patients with chronic kidney disease.
Keywords: Pregnancy Proteins; dospělí; studie případů a kontrol; Humans; lidé středního věku; Middle Aged; chronická renální insuficience; Renal Insufficiency, Chronic; zánět; Lipids; mužské pohlaví; Adult; Placenta Growth Factor; biologické markery; Dyslipidemias; C-reaktivní protein; Inflammation; ženské pohlaví; dyslipidemie; Female; těhotenské proteiny; lidé; C-Reactive Protein; Case-Control Studies; placentární růstový faktor; Biomarkers; Aged; senioři; Male; lipidy